Effects of grassland burning on reproductive success of globally threatened Strange-tailed Tyrants Alectrurus risora - Di Giacomo, Alejandro G. (2011)
The north-east of Argentina contains a high number of globally threatened grassland birds and is increasingly managed for livestock, with annual burning in remaining natural grasslands. The Strange-tailed Tyrant Alectrurus risora, a globally threatened grassland specialist, has suffered a 90% contraction in its original range. From 1996 to 2008 we monitored a breeding population in Formosa, north-east Argentina, and explored the effect on breeding of four accidental and one prescribed fires. The plant most frequently used for nesting was Imperata brasiliensis, but the frequency of use was lower after a fire than before. In years with a fire, the height of the plant used for nesting and the height of the nest were lower than in those without a fire. Females avoided nesting in the burned plot in the breeding season immediately after the prescribed fire, but they started to return to the burned plot by the second breeding season and did not discriminate between plots by the third breeding season after the fire. Movements of females after the prescribed fire did not affect nest survival, clutch size, hatchability or chick survival indicating this species was adapted to regular fires. However, our results also show that annual burning in the grassland negatively affects the settlement for reproduction of Strange-tailed Tyrants and that the intervals between burns in the same grassland should be longer than two years.